(untitled) (Eurasian Journal of Ecology, 2016)
In work features of structure of communities of ground macroinvertebrate mountain water currents ofAltai which is in a zone of influence of the mining enterprises are analysed. Decrease in the general specific riches of ground communities, reduction of number of kinds sensitive to pollution таксономических groups of macroinvertebrates (веснянок, green drakes, caddis flies) on the sites subject to pollution isn’ted. The estimation of an ecological condition of water currents is given.